2011
DOI: 10.1016/j.jclinepi.2010.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis Index delivered by mobile phone (m-WOMAC) is valid, reliable, and responsive

Abstract: There was close agreement and no significant differences between m-WOMAC and p-WOMAC scores. This study confirms the validity, reliability, and responsiveness of the Exco InTouch-engineered, Java-based m-WOMAC Index application. EDC with the m-WOMAC Index provides unique opportunities for using quantitative measurement in clinical research and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 30 publications
3
50
0
Order By: Relevance
“…A similar result has been shown using a randomized order of presentation design in a comparison of a mobile phone-based version of the WOMAC NRS 3.1 Index and a paper version (33). However, a limitation of the current study was that completion on paper or electronic media first or second was not randomized.…”
Section: Discussionsupporting
confidence: 62%
“…A similar result has been shown using a randomized order of presentation design in a comparison of a mobile phone-based version of the WOMAC NRS 3.1 Index and a paper version (33). However, a limitation of the current study was that completion on paper or electronic media first or second was not randomized.…”
Section: Discussionsupporting
confidence: 62%
“…Bellamy et al (Level of Evidence:4) tested a version of the mobile WOMAC index (m-WOMAC) with older adult patients (n=12), who regarded the system as easy to use (Very easy:11/12) and acceptable for use (Very confident in continued use: 11/12), with the index being transmitted successfully[48]. Other studies (n=62, n=12) found a high agreement between paper and mobile versions of the WOMAC index (Level of evidence: 4, 4; Correlation: 0.90+, 0.996), and found that the favorable reviews by participants and the effectiveness of the platform held across multiple phones[49,50]. …”
Section: Resultsmentioning
confidence: 99%
“…Frequently discussed problems in assessing electronic PRO data include patient age and related computer literacy [10,[21][22][23][24], as well as the additional time and burden for the patient and healthcare institutions in supplying electronic devices and giving instruction on their use [22,[25][26][27][28][29]. However, this study showed that age was not a factor.…”
Section: Discussionmentioning
confidence: 81%